Ultraviolet Radiation and its Germicidal Effect in Drinking Water Purification - P. Ponmurugan3; B. Mythili Gananamangai3*, K.M. Johnson1, M.R. Anil Kumar2 (Journal of Phytology, 2010)
Microbial disinfection using ultraviolet radiation is a world wide technology for drinking water purification. The effectiveness of this technology depends on certain important parameters like the UV intensity, the exposure time, the area, clarity of the water etc. This technology is very convenient and fast, doesnâ€™t alter the taste of the water or adding chemicals into the water.Â The selection of UV wavelength is very important for the efficient disinfection process. The optimum microbial killing efficiency ranges from 254 to 260 nm wavelength probably varies with the type of organism. Viruses and bacteria in vegetative forms are most sensitive to UV radiation. It gives in-depth review of ultraviolet (UV) light for using as a disinfection technology in potable water supplies. This paper is intended to assist the reader in evaluating the disinfection capabilities of UV light to inactivate disease-causing bacteria, viruses, and cysts.